2021
DOI: 10.3389/fpsyg.2020.601104
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Creativity and Intrusive Rumination Among Chinese Teenagers During the COVID-19 Pandemic: Emotional Resilience as a Moderator

Abstract: Coronavirus disease 2019 (COVID-19) has not only resulted in immeasurable life and property losses worldwide but has also impacted individuals’ development, especially teenagers. After the COVID-19 pandemic, individual rumination as an important cognitive process should be given more attention because of its close associations with physical and mental health. Previous studies have shown that creativity as an antecedent variable can predict people’s mental health or adaptation. However, few studies have focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 95 publications
1
16
1
Order By: Relevance
“…Resilience and meaning in life served as protective factors for mental health [ 37 ]. Furthermore, in a study in 1488 Chinese teenagers, creative ideational behavior was positively related to intrusive rumination during the pandemic [ 38 ]. Interestingly, like Liang et al [ 31 ], resilience and creativity were associated.…”
Section: Part Ii: Systematic Literature Searchmentioning
confidence: 99%
“…Resilience and meaning in life served as protective factors for mental health [ 37 ]. Furthermore, in a study in 1488 Chinese teenagers, creative ideational behavior was positively related to intrusive rumination during the pandemic [ 38 ]. Interestingly, like Liang et al [ 31 ], resilience and creativity were associated.…”
Section: Part Ii: Systematic Literature Searchmentioning
confidence: 99%
“…In particular, professionals in creative fields (e.g., writing) tend to ruminate ( Tsai et al, 2021 ). Some studies have also investigated that students’ creativity during an pandemic is positively associated with invasive rumination ( Wang et al, 2021 ). Based on this argument, we propose the following hypothesis.…”
Section: Theoretical Foundations and Assumptionsmentioning
confidence: 99%
“…Specific aspects of creativity—namely flexible thinking and originality—appear most pertinent to the process of emotional resilience, and a high level resilience can help individuals maintain a good state in traumatic events, thus providing good conditions for the development of creativity ( Metzl, 2009 ). The relationship between these two variables has been little explored; however, the studies that have reached similar conclusions ( Wang et al, 2021 ). In summary, we propose the following hypothesis:…”
Section: Theoretical Foundations and Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, creative ideas and material from life can be obtained through rumination (Forgeard et al, 2020). It has been shown that intrusive rumination is positively correlated with creativity (Wang et al, 2021) and that intrusive rumination may promote deliberate rumination (Kamijo and Yukawa, 2018). Deliberate rumination indicates that individuals cognitively revisit events, reframe and recover their core beliefs, and feel positive changes in several aspects of their lives (Cann et al, 2011).…”
Section: Introductionmentioning
confidence: 99%